Estrogens Promote the Production of Natural Neutralizing Antibodies in Fish through G Protein-Coupled Estrogen Receptor 1 - Rodenas, María C.; Cabas, Isabel; Gómez-González, Nuria E.; Arizcun, Marta; Meseguer, José; Mulero, Victoriano; García-Ayala, Alfonsa (Frontiers in Immunology, 2017)
Natural antibodies play crucial roles in pathogen elimination, B-cell survival and homeostasis, and inflammatory and autoimmune diseases. Although estrogens are able to regulate both innate and adaptive immune responses, their role in the production of natural antibodies is unknown. Here, we show that the dietary intake of the synthetic estradiol analog, 17α-ethinylestradiol (EE2), one of the most potent pharmaceutical estrogens and intensively used in human therapeutics as a component of most oral contraceptives, regulates the abundance and proliferation of T and IgM+ B lymphocytes in the teleost fish gilthead seabream (Sparus aurata L.). Furthermore, for the first time in vertebrates, it is shown that estrogen signaling through G protein-coupled estrogen receptor 1 (GPER1) induces the production of polyreactive natural antibodies, which are able to crossreact with unrelated antigens and commensal and pathogenic bacteria. In addition, the serum from fish treated with EE2 or the GPER1 agonist G1 shows higher complement-dependent bactericidal activity than that from non-treated specimens. These results demonstrate that estrogens and GPER1 are the key regulators of natural antibody production and pathogen clearance in fish, paving the way for future studies in other vertebrate classes.